Endo-Activators for A Successful Endodontic Treatment - Raddawi, Ammar Al; Mobayed, Mazen; Tevzadze, Veriko (Caucasus Journal of Health Sciences and Public Health, 2019)
The subject that will be reviewed is carrying a type of revolutionary character in therapeutic operative dentistry in general, and it represents the field of endodontic treatment. As in all disciplines of dental medicine, evolution of this field has started from the day of its development, and as a rule in any type of evolutionary processes, there were certain key points during this path. In our case it is the period during problems were actively existent and reaching certain objectives such as: cleaning and shaping the root canal accurately for obturation, removal of the smear layer completely, reaching out to additional root canals, delta canals, and accessory canals in keeping care of the apical foramen and preventing complications like, over irrigation (high toxicity), substances passing to the surrounding tissues, basically reaching an optimum result after the endodontic treatment.